APLIKASI SISTEM MANAJEMEN KEAMANAN INFORMASI BERBASIS ISO 27001 : 2013 MENGUNAKAN FRAMEWORK LARAVEL - Adam Baryadi Pramono (2022)
The plurality of information, the crucial impact of information dissemination, as well as cybercrimes, are some of the many reasons why each data and information storage unit and system. For its availability, its accuracy and integrity must be maintained, or what is commonly abbreviated as CIA (confidentiality, integrity, and availability). To ensure the existence of the CIA in information, especially in a state agency or company in general, it is necessary to have an Information Security Management System (SMKI). This Information Security Standard is called ISO 27001. Researchers start the research by collecting data, including literature studies to identify problems. After that, the author uses the waterfall application development method as the basis for making applications. The results of the study are in the form of an index or score, which will be displayed according to indicators taken from the ISO 27001:2013 standard and are web-based, which will make it easier to modify.